THE EFFECT OF USING REDW STRATEGY ON STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT AT THE X GRADE OF SMA NEGERI 1 AIR JOMAN IN 2022/2023 ACADEMIC YEAR - ORIANA LESTARI; LIS SUPIATMAN; PUTRI LIDIANA PERMATA SARI (LINGUISTICA, 2023)
This research was meant to find out the empirical evidence of the students' accomplishment in reading comprehension of narrative text by utilizing Read Examine Decide Write (REDW) Strategy at the X Grade of SMA Negeri 1 Air Joman. This research was quantitative research. The entire class of students at SMA Negeri 1 Air Joman's grade X made up the population of this study. 30 students from the experimental group (class X IPA 4) and 30 students from the control group served as the research's sample subjects (class X IPA 1). A test with multiple choices was used to obtain the data. (1) The students' achievement in reading comprehension narrative text by utilizing the Read Examine Decide Write (REDW) Strategy got the post-test with an average result after the data was analyzed. (1) The students' accomplishment in reading comprehension narrative text by utilizing the Read Examine Decide Write (REDW) Strategy got the post- test with an average result of 83 after the data was analyzed (2) The post-test showed that the students had successfully read narrative texts with comprehension using the conventional way, with an average score of 67. The value of t-observed was 8,43 and t- table was 2,009. The fact that the value of t-observed was higher than t-table indicates that the Read Examine Decide Write (REDW) Strategy had a significant impact on students' reading comprehension success.